Smart Helmet - Mohd Yusof, Mohammed Syahid Nafi' (Universiti Teknologi PETRONAS, 2009)
This report is written for the purpose of highlighting the background of the research project for the SMART HELMET, the scope of the study, research method and the literature review. SMART HELMET is a system which aims to make all motorcyclists in Malaysia aware and compulsory to wear helmet whether the travel distance is in I 00 meter radius or long distance. The system will use ~ee technology which will connect from the transmitter at helmet to the receiver at motorcycle. Many type of switches being used such as temperature heat switch, clipped switch, and signal as a switch to make sure the motorcyclist not cheating to their self. If the system identified that the riders or user not wearing their helmet properly (clipped), the signal won't be send to the receiver at motorcycle which will cause the motorcycle can not start and being ride by motorcyclist. The scope of the study will be using others studies and statistics from Malaysia government agencies in term of Road Safety; fatal motorcyclist accident causes and focus on the helmet wearing attitude and behavior. The scope also will cover on research of overview XJ3~e_ l Technology applications, behavior, characteristics as well as advantages and disadvantages of X.Bee_ . Technology. Then will cover on implementation of the system in real daily life.